Proposta de implantação de um escore de alerta precoce em uma enfermaria pediátrica - Cavalcante, Sandra Ávila (2024)
The aim of this study was to propose the implementation of the Pediatric Alert Score in a pediatric inpatient unit of a teaching hospital. This is a convergent care study with a qualitative and quantitative approach. Nurses, doctors, physiotherapists and children took part in the study. Data collection took place between September 2023 and January 2024, in four stages. In the first stage, the pre-test questionnaire was applied, training was given on the Pediatric Alertness Score followed by a post-test; in the second stage, the professionals applied the score with the children on the ward; in the third stage, the Convergent Group met and in the fourth stage, the semi-structured interview was carried out. The analysis and interpretation of the results followed the apprehension stages, using Atlas.ti® software for the qualitative data and SPSS® software for the statistical tests. In the synthesis, the following categories emerged: experience of applying the Paediatric Alert Score in the ward and Challenges for implementing the Paediatric Alert Score in the sector. In the theorization, the conclusions about the application of the score were organized. The project was approved by the Research Ethics Committee of the Federal University of Rio Grande do Norte under opinion No. 6.228.211. The results showed that 91.67% of the professionals were female, 83.33% nurses, 50% specialists, with a minimum training period of 10 years. Of the children, 57.14% were female, 28.57% were between six and 10 years old, 48.56% were diagnosed with renal and neurological disease, and 90% had comorbidities. The application of the Pediatric Alert Score on the ward showed a prevalence of ≥ 3 of 14.21%, with 80% of moderate to severe signs present in the < 2 year age group, with no gender inference. It was observed that all the professionals recognized the warning signs, however they mentioned work overload, poor equipment and lack of knowledge on the subject as factors that made it difficult to recognize deterioration. Of these professionals, 91.7% agreed that assessment instruments contribute to recognizing a serious situation; however, none of the instruments mentioned corresponded to early warning scales, since 66.66% said they had no knowledge of pediatric warning scores. After the educational intervention, there was a change in the number of correct answers in the post-test from 55% to 80%, which shows that there is a need for continuing education in the sector to solidify professionals' knowledge. The convergence group and interviews showed that the score is effective, easy to apply, easy to understand, quick to use and of important use to the interdisciplinary team. However, routine, staffing, relationships and interprofessional communication were factors that hindered the feasibility of its use on the ward. The workshop on the Early Warning Score had a positive impact on post-training knowledge, as the score was effective in identifying signs of deterioration in children. The commitment, engagement and monitoring of management and the multi-professional team are essential for the effective implementation of the pediatric alert score in the institution.